Analisis Perbedaan Kelengkapan Pengisian Asesmen Medis Gawat Darurat Elektronik dengan Manual pada Diagnosis Skizofrenia Tak Terinci di RSJD Surakarta - Ratna Komala Sari; Sri Sugiarsi; Sri Mulyono (Lembaga Penerbitan Universitas Esa Unggul, 2023)
AbstractBased on the preliminary survey at RSJD Surakarta from 10 electronic emergency medical assessments, the lowest completeness was on the item verification date, 70%. In contrast, the manual item for patient history and psychiatric examination was 80%, and the doctor's name item was 90%. This study aimed to determine the differences in the completeness of filling out electronic emergency medical assessments with manuals on an unspecified diagnosis of schizophrenia at RSJD Surakarta. This type of research is comparative. The research design uses a retrospective approach. The population of all electronic and manual emergency medical assessment forms for the diagnosis of schizophrenia is not detailed in the third quarter of 2021 and 2019. The sample size is 62, taken using a simple random sampling technique. The method of collecting data is by observation and unstructured interviews. The instrument uses an observation sheet and unstructured interview guidelines. Analysis of the data used is Mann Whitney test. The results of the complete identification of electronic and manual emergency medical assessments were 100%. The completeness of the important electronic emergency medical assessment reports was 77.42%, while the manual was 61.29%. The completeness of the electronic emergency medical assessment authentication is 100%, while the manual is 90.32%. Based on the results of the study, it is recommended that medical record officers coordinate with the SIMRS section when the verification date has not been filled in, the server cannot be saved, provide socialization about the importance of writing vital signs to determine the patient's health condition and improve the completeness of the medical record.Keywords: analysis, completeness, electronic emergency medical assessment filling by manualAbstrakBerdasarkan survey pendahuluan di RSJD Surakarta dari 10 asesmen medis gawat darurat elektronik kelengkapan terendah pada tanggal verifikasi 70% sedangkan manual pada riwayat pasien dan pemeriksaan psikiatri 80%, serta nama dokter 90%. Tujuan penelitian ini untuk mengetahui perbedaan kelengkapan pengisian asesmen medis gawat darurat elektronik dengan manual pada diagnosis skizofrenia tak terinci. Jenis penelitian yaitu komparatif. Populasinya adalah seluruh formulir asesmen medis gawat darurat elektronik dan manual pada diagnosis skizofrenia tak terinci triwulan III tahun 2021 dan 2019. Besar sampel adalah 62, diambil dengan teknik simple random sampling. Cara pengumpulan data melalui observasi dan wawancara tidak terstruktur. Uji mann whitney digunakan untuk menganalisis perbedaan kelengkapan formulir elektronik dan manual. Hasil penelitian menunjukkan bahwa identifikasi asesmen medis gawat darurat elekronik dan manual lengkap 100%. Laporan penting asesmen medis gawat darurat elektronik; lengkap sebanyak 77,42%, sedangkan manual 61,29%. Autentifikasi asesmen medis gawat darurat elektronik lengkap 100%, sedangkan manual 90,32%. Terdapat perbedaan kelengkapan formulir elektronik dengan yang manual pada nilai p=0.033(<0.05).Kata Kunci: analisis, kelengkapan, pengisian asesmen medis gawat darurat elektronik dengan manual